EXPLORING CONTROL ENVIRONMENT PRACTICES IN LOCAL GOVERNMENT-OWNED COMPANIES - Muhammad Ridwan Arif; Andi Abdul Azis Ishak; Tamrin Tamrin; Muhammad Jayadi (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
This study investigated and evaluated the implementation of governance practices concerning the control environment in government-operated water supply firms in South Sulawesi Province, Indonesia. The objective of this study was to ascertain the most effective methods for implementing governance within government-owned firms. It also examined the maturity level of the control environment. This study utilized the multiple case study method and focused on three observed organizations. The qualitative data was analyzed using implementation-level assessment and comparison analysis across the cases. Multiple discoveries were unveiled in this investigation. Initially, the implementation of a control environment in observed organizations was rudimentary. Furthermore, effective communication and coordination across pertinent departments enhanced control consciousness inside the organization. Furthermore, this study recognized the significance of employing a procedural selection process for audit firms. Nevertheless, multiple domains necessitate enhancement to augment the quality of governance, specifically recognizing the significance of risk management and compliance programs. Additional aspects that may arise in control environment practices, such as corporate culture and political difficulties, should be further investigated.